Pengaruh Faktor Eksternal Terhadap Kualitas Audit pada Perusahaan Subsektor Perbankan yang Terdaftar di Bei Periode 2021- 2023 - Sinaga, Tri Laura Tresia; Astuti, Tutut Dewi (CV. ITTC INDONESIA, 2024)
This study aims to analyze the influence of external factors on audit quality in banking subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The external factors analyzed include audit fees, audit tenure, and audit committees. This research uses a quantitative method with a purposive sampling approach, where the research sample consists of banking subsector companies listed on the IDX that meet certain criteria. The data used are secondary data in the form of financial statements obtained from the official IDX website. Data analysis was conducted using logistic regression with SPSS software. The results of the study show that audit fees and audit tenure do not have a significant effect on audit quality. Similarly, the presence of an audit committee also does not have a significant effect on audit quality. These findings provide new insights into the need for a deeper evaluation of the factors influencing audit quality in the banking sector, especially given the critical role of banking institutions in national economic stability.